Mechanisms to combat Illegal immigration at the International and Regional Levels - Abdullah, Rand; Muslim, Nibras (Journal of Legal Sciences, 2023)
The phenomenon of illegal immigration is a global phenomenon that threatens the security and stability of the majority of countries. This matter prompted the international community to exert efforts and cooperate in order to combat it or reduce its effects. This was done through the development regional levels to eliminate the phenomenon of illegal immigration.